Pengembangan Game Content Model Untuk Game-Based Learning Pemahaman Berlalu-Lintas - Riska Nurtantyo Sarbini; Purnomo Budi S.; Onny Setyawati (Fakultas Teknik, Universitas Brawijaya, 2015)
This paper describes the application of the Game Content Model (GCM) in Role Playing Games (RPG) for the understanding of the traffic using a quest-driven learning. One key GCM models, namely the Game Object with intelligence component was applied using dynamic pathfinding capabilities of artificial intelligence in non playable character (NPC). NPC used the A * algorithm as the basis of the nearest search capability to the target.Index Terms—Game,GCM,RPG,A* Algorithm